The scope of creative commons licenses for sharing and using research data within an institutional repository (Ius Novum, 2022)
The purpose of this article is a civil analysis of the scopes of authorizations containedin creative commons licenses in the context of their potential use in the activities ofan institutional repository. The reference point for the considerations are also the conditionsfor sharing and transferring public sector information for re-use set out in the Open DataAct of 2021. The material, temporal and territorial scope of the Creative Commons licenseshas been specified. The task requires, in particular, the examination of the standards of openlicenses in the light of the provisions of the Copyright Act of February 4, 1994 and the Act ofJuly 27, 2001 on the protection of databases. It seems significant in the context of the problemsregarding to the functioning of the Creative Commons licenses under Polish law. This typeof analysis seems all the more justified because in the case of research data, the subject ofthe authorization may not only be a work, but a database or the subject of related rights. In thecourse of the research, the dogmatic-legal and legal-comparative methods were mainly used.It should be concluded that the reference to standard open Creative Commons licensesenables the obliged entity to properly fulfill its obligations to define the content of the conditionsfor re-use specified in particular in Art. 15 of the Act on Open Data of 2021. The presentedprinciples of recognition of authorship satisfy the obligation to inform about the source andtime of generating and obtaining public sector information from the obliged entity. In turn,the obligations relating to the exploitation of derivative works specify the conditions forthe obligation to inform re-used public sector information about the processing. It should berecognized that referring to the Creative Commons licenses within institutional repositoriesmay be appropriate, taking into account the indicated shortcomings, discrepancies and the lackof full synchronization of the developed international standards with the Polish legal order.
Keywords: creative commons; license; institutional repository; research data; open data